Increase The Financial Literacy of Small and Medium-sized Enterprises (SMEs) Through Game-based Learning - Rizky; Senie Destya; Wiji Nurastuti; Ayu May Lestari (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Muara Kuin is a boardgame used to teach financial literacy through game-based learning to SMEs owners around Special Region of Yogyakarta. The purpose of this study was to determine the impact of Muara Kuin on people's financial literacy abilities and knowledge. This study is a quantitative and qualitative research project that collected 30 samples from the general public. Data was collected through a survey used random sampling, an interview used purposive sampling, and tested by Paired Sample T Test. Following that, 5 people are chosen to be interviewed about their ability to manage finances while playing the game. According to the findings of the study, Muara Kuin give impact to financial literacy knowledge and ability of strategy financial literacy.